Guru SD Sebagai “Model” Dalam Meningkatkan Indigeneousasi Pada Siswa Sekolah Dasar - Anak Agung Putu Sugiantiningsih; Yossita Wisman; Cukei (Jurnal Ilmiah Kanderang Tingang, 2023)
Formal education in Indonesia starts from elementary school level. In elementary school, students experience development in the personal-social (personal-social development), academic (academic development) and career (career development) aspects, so that they become a generation of a nation that is independent and actively develops its potential, has religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by himself, society, nation and state. The development of elementary school students, apart from their families, is influenced by the school/educational environment. For example, elementary school students are very obedient to what their teachers say, because elementary school teachers, for them, are figures they "look up to and imitate". A professional teaching model can have a positive effect on children's development. However, there are quite a few elementary school teachers who have negative effects, such as when teaching and learning activities are fierce/like to punish if students answer incorrectly, impose their will, don't care about students' needs, feel they know best and so on. This example of an unprofessional elementary school teacher model will certainly hinder student indigenousization so that student potential does not develop optimally. In relation to student indigenousization, there is a need for teachers who can be used as "models with character" (Bandura's theory) who can provide educational learning and motivate elementary school children to develop their indigenousization. The character model in question is a teacher who has competence as an educator, namely pedagogical, personal, social and professional competence.